Maternal Perceived Stress, HIV Status, and Feeding Styles are Predictors of Infant Dietary Intake in Ghana - Adhikari, P.; Marquis, G.S.; Lartey, A. (African Journal of Food, Agriculture and Development, 2023)
Indicators of poor maternal mental health have been associated with non-responsive feeding styles that affect dietary intake in infants. This study examined the association between maternal mental health indicators and infant dietary intake and infant feeding behaviors within a 2003 to 2008 longitudinal observational cohort study in Ghana (the Research to Improve Infant Nutrition and Growth [RIING] project). A random sample of one third of the RIING cohort (19 HIV positive [HIV-P], 29 HIV negative [HIV-N], and 24 HIV unknown [HIV-U]) and their infants was selected for an in-home 24-hr weighed dietary study at 9 months postpartum. Maternal depressive symptoms and perceived stress scores had been measured at 6 months using the Edinburgh Postnatal Depression Scale (EPDS) and Perceived Stress Scale (PSS), respectively. All foods and liquids were weighed to determine energy and nutrient intake values. Human milk intake was weighed. Each feeding session was observed, and the feeding style was recorded. Multiple linear regression showed that maternal perceived stress was negatively associated with total food (-12.4 g, 95% CI: -21.0 to -3.8), energy (-19.5 kcal, 95% CI: -33.8 to -5.2), and fat (-0.7 g, 95% CI: -1.4 to -0.1) intake from complementary foods and liquids in infants. An HIV-P status was associated with a lower intake of fat (-6.3 g, 95% CI: -11.1 to -1.5) and vitamin A (-293.9 µg, 95% CI: -529.9 to - 57.8) compared to HIV-N. Maternal mental health indicators were not associated with feeding style. However, a positive feeding style was associated with a higher intake of fat (4.8 g, 95% CI: 0.3 to 9.2) and vitamin A (245.3 µg, 95% CI: 28.2 to 462.5) compared to a passive feeding style. This study highlights the importance of focusing on how the infants are fed during the complementary feeding period. Interventions to improve infant dietary intake should prioritize maternal mental health and promote positive feeding styles among high-risk caregivers
Research Article
Keywords: maternal depression; perceived stress; HIV